Tau oligomers mediate aggregation of RNA‐binding proteins Musashi1 and Musashi2 inducing Lamin alteration. Issue 6 (18th September 2019) - Montalbano, Mauro; McAllen, Salome; Sengupta, Urmi; Puangmalai, Nicha; Bhatt, Nemil; Ellsworth, Anna; Kayed, Rakez
Abstract: The exact mechanisms leading to neurodegeneration in Alzheimer's disease (AD) and other tauopathies are not yet entirely understood. However, it is known that several RNA‐binding proteins (RBPs) form toxic aggregates and also interact with tau in such granules in tauopathies, including AD. The Musashi (MSI) family of RBPs, consisting of two homologues: Musashi1 and Musashi2, have not been extensively investigated in neurodegenerative diseases. Here, using a tau inducible HEK (iHEK) model we investigate whether MSI proteins contribute to the aggregation of toxic tau oligomers (TauO). Wild‐type and mutant P301L tau iHEK cells are used to study the effect of different tau variants on the cellular localization of MSI proteins. Interestingly, we observe that tau co‐localizes with MSI in the cytoplasm and nuclei, altering the nuclear transport of MSI. Furthermore, incremental changes in the size and density of nuclear MSI/tau foci are observed. We also report here that TauO interact with MSI to cause the formation of distinct nuclear aggregates. Moreover, tau/MSI aggregates induce structural changes to LaminB1, leading to nuclear instability. These results illustrate a possible mechanism of neurodegeneration mediated by the aggregation of MSI proteins and TauO, suggesting that MSI plays a critical role in cellular dysfunction. Abstract : Tau modulates expression and nuclear translocation of RNA‐binding proteins Musashi. Tau and Musashi proteins form nuclear aggregates. Toxic interaction of tau with Musashi induces nuclear lamina dysfunction.